KINERJA KEUANGAN DENGAN PENDEKATAN FINANCIAL RATIO DAN MARKET RATIO PADA PT ASTRA INTERNASIONAL, Tbk. PERIODE TAHUN 2014-2019 - yulius gessong sampeallo; Fariyanti Fariyanti; Nurul Hidayah (Politeknik Negeri Samarinda, 2020)
The purpose of this study was to determine the financial performance of PT Astra International Tbk in the 2014-2019 period with the Financial Ratio approach and to determine the financial performance at PT Astra Internasional Tbk in the 2014-2019 period with the Market Ratio approach.The analytical tool used is the Financial Ratio approach in terms of liquidity ratios, solvency ratios, activity ratios and profitability ratios and the Market Ratio approach in terms of earnings per share, price earning ratio, dividend yield, dividend payout ratio and price to book value ratio. The results of the analysis of financial ratios show that the financial performance of PT Astra International, Tbk has fluctuated from the Financial Ratio approach in terms of liquidity ratios consisting of current ratios of 1.29 times and quick ratios of 1.05 times, solvency ratios consisting of debt to asset ratios of 46.94% and debt to equity ratio of 88.45%, the activity ratio consists of inventory turnover of 9.34 times, fixed asset turnover of 3.80 times and total asset turnover of 0.67 times and ratio profitability consists of return on assets of 7.56% and return on equity of 14.25% and experiencing fluctuations from the Market Ratio approach in terms of earnings per share ratio of Rp 536.19, price earning ratio of 12.92 times, dividend yield of 3.05%, dividend payout ratio of 39.38% and price to book value ratio of 1.50 times.Keywords: Financial Performance, Financial Ratio and Market Ratio